Dinâmica do sistema estuarino Timonha/Ubatuba (Ceará - Brasil): considerações ambientais - Braga, Carolina Dias (2005)
The Timonha / Ubatuba estuarine system is located between Ceará and Piauí States, 500 km northwest of Fortaleza City, in Northeast Brazil. The hydrographic tributary basin of this estuarine system has an area of 2 165 km2, and lies in Paleozoic lands of the Ibiapaba Plateau, Embasamento Cristalino, Formação Barreiras and Quaternary deposits. It is important to stand out that the south portion of this estuarine basin is inserted in Pre-Cambrian lands where may be seen Granitóide Chaval exhumed inside of the system. The search for areas suitable to shrimp farming and urban/agroindustrial development may represent a potential risk to this ecosystem, which is considered the largest of the Ceará State. These impacts tend to increase with the construction and operation of the Itaúna reservoir, with a capacity of 77.5 million m3 and located 17 km from the estuarine basin. The aim of this study was considering the structural, dynamic and controlling elements of the current state of the estuarine system, to contribute with useful information to the suitable and sustainable use of this ecosystem. The hydrodynamic and sedimentologic processes are dominated by the rainy seasons plus the sedimentation processes on the mouth by longshore current and tide oscillation. The reservoir resulted in the reduction of 91% of the Timonha river discharge presenting an outflow of 5.6 X 108 m3 in a year. The regularized outflow is not enough to promote the mixing and salt dilution processes, contributing to the inversion of salinity in the drought season. In the rainy season, the salinity of Timonha River grows gradually seaward and varied from limnetic (< 0.5) to euhaline (30.0 at 40.0). In the dry season, predominated the euhaline pattern with strong signals of hipersalinization. In Ubatuba river, the salinity varied from polihaline (18.0 at 30.0) to euhaline between the rainy and drought periods. The estuaries are type 2a in the rainy period and 1a in the drought period. The salt balance of Timonha river in the rainy period was + 0.3 ton, while in the dry period was 0.0 ton. In Ubatuba river the salt balance was - 0.1 ton and in the dry period was - 0.2 ton. The average depth of the system is 5 m and the deeper depths were seen in Ubatuba river. The bottom is made up predominantly by medium sand and biogeneous sediments. The total of sediments exported to the longshore current, in a year, was 250 tons and the load imported was 150 tons. The volume of the tide prism in Timonha river was nearly 3.6 x 107 m3 and in Ubatuba river 4.3 x 107 m3. Considering the simplified model, the period of water residence is 1 day in the rainy period and 5 days in dry period. This period, in Ubatuba river, is 0.5 day in the rainy period and 2 days in the dry period. Considering the water residence time calculated to each segment of the channels of Timonha and Ubatuba Estuaries, it was observed that the linear model is not applicable to the system dilution capacity analysis. Based on the segmented model, it was verified, in Timonha river, that the area located between 3,7 km and 7,0 km from the sea, has a strong tendency to water retention and reaches a residence time equivalent to almost a week, been inadequate to the direct emission of effluent. Comparing to other tropical estuaries, the system presents a good dilution capacity and a low residence time. The lack of monitoring to correct the outflows released by Itaúna Dam in long dry periods and the deposition processes on the mouth river will represent the main elements to jeopardize the support capacity of the estuary.